ROLE OF FOREIGN LANGUAGE TEACHING ENJOYMENT ON BURNOUT AND RESILIENCE: RESULTS FROM EFL TEACHERS - Aghayani, Behnam; Mohamadi, Samira; Rekabizadeh, Forough; Bakhtiari, Mahsa (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Foreign language teachers often face distinct challenges in their professional journey, which can lead to burnout and decreased resilience. Foreign Language Teaching Enjoyment (FLTE) is an emotion that can help teachers overcome such challenges and difficulties. This study firstly examines the relationship between EFL teachers’ FLTE and their burnout, and secondly explores the relationship between EFL teachers’ FLTE and their resilience. The study also investigates the influence of EFL teachers’ FLTE on their burnout. The participants were 204 Iranian EFL teachers, comprising 140 females and 64 males. In the data collection, the participants responded to three online questionnaires, namely the Foreign Language Teaching Enjoyment Scale (FLTES), the Burnout Scale, and the Resilience Scale. The results of Pearson product-moment correlation indicated that EFL teachers’ FLTE was associated with both their burnout and their resilience. Moreover, the regression analysis showed that EFL teachers’ FLTE significantly predicted their burnout. The findings can help teachers set up a successful teaching and learning environment by boosting their sense of well-being. Education stakeholders can also utilize these findings to improve job satisfaction.